The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/ene.12344
|View full text |Cite
|
Sign up to set email alerts
|

A phase II−III trial of olesoxime in subjects with amyotrophic lateral sclerosis

Abstract: Olesoxime, although well tolerated, did not show a significant beneficial effect in ALS patients treated with riluzole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 25 publications
2
82
0
Order By: Relevance
“…The statistical MUNE method was used in the unsuccessful multicenter creatine study, and it became clear that the method was limited as it does not account for motor unit variability as seen as advanced disease [95]. Other methods of motor unit assessment have been used in single trials of memantine [96], but methods of assessing motor units were not used in 2 recent, large international phase IIb multicenter studies [20,21], nor other recent exploratory phase II studies [22,97,98]. The discussion of MUNE at recent meetings has been limited; for example, MUNIX was the only method discussed at the recent International ALS/Motor Neurone Disease Symposium in December 2015 [99].…”
Section: Als Clinical Trialsmentioning
confidence: 99%
“…The statistical MUNE method was used in the unsuccessful multicenter creatine study, and it became clear that the method was limited as it does not account for motor unit variability as seen as advanced disease [95]. Other methods of motor unit assessment have been used in single trials of memantine [96], but methods of assessing motor units were not used in 2 recent, large international phase IIb multicenter studies [20,21], nor other recent exploratory phase II studies [22,97,98]. The discussion of MUNE at recent meetings has been limited; for example, MUNIX was the only method discussed at the recent International ALS/Motor Neurone Disease Symposium in December 2015 [99].…”
Section: Als Clinical Trialsmentioning
confidence: 99%
“…Among the candidates were: gilenya (Novartis AG), approved to treat multiple sclerosis, the epilepsy drug retigabine (Valeant Pharmaceuticals International Inc.), actemra (Genentech/Roche AG), approved to treat rheumatoid arthritis, ozanezumab (Glaxo smithkline), an immune modulator now in a phase II program, and NP001 (Neuraltus Pharmaceuticals Inc.), which is in phase II clinical trial, for slowing down the progression of ALS. Also on the list was nurown Recently, olesoxime (Roche AG) [197,198] and dexpramipexole (Biogen Inc.) [199,200] have been included as lead compounds. Moreover, tirasemtiv (Cytokinetics Inc.), a fast skeletal muscle troponin activator was granted a second opportunity after a phase II failure with a reconfigured phase III trial [201,202].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In superoxide dismutase transgenic mice (SOD1 G93A ), a widely used model of ALS, olesoxime has improved motor neurons performance and has delayed the onset of the disease phenotype [32,37]. Unfortunately, in a phase III clinical trial, olesoxime has failed to produce a significant benefit, compared with placebo treatment in ALS patients [38]. Recently, Barron et al [39] have reported the neuroprotective effects of Ro5-4864 in a mouse model of AD.…”
Section: Tspo Ligands In the Treatment Of Neurodegenerative Diseasesmentioning
confidence: 99%